Institutional Quality and Macroeconomic Determinants of Diaspora Remittances Inflow in Nigeria - I. M. , Ochada (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2020)
The study examined the institutional quality and macroeconomic determinants of diaspora remittances inflow in Nigeria, via autoregressive distributed lag model (ARDL) from 1981-2017. The ARDL bound cointegration test showed that a long-run relationship exists among institutional quality and macroeconomic determinants of remittance inflows in Nigeria. That is, there is a long-run implication of GDP, exchange rate, inflation rate, interest rate, unemployment, and net migration on the remittances inflows in Nigeria. Besides, the findings demonstrated that both in the short and long-run institutional quality and macroeconomic determinants of remittances have a significant relationship with the remittance’s inflows in Nigeria. While GDP per capita, inflation rate, and interest rate exert a negative effect, exchange rate and net migration exhibit a positive significant link with remittances inflows. It is suggested and concluded that to pull in more remittances, policymakers should think progressively about actualizing steady and master development strategies. It is, consequently, prescribed to devise procedures planned for accomplishing a higher and continued pace of financial development, improved institutions in form of regulatory quality, control of corruption, political stability, and stability of macroeconomic variables in Nigeria.